The effect of L-Lysine in recurrent herpes labialis: pilot study with a 8-year follow up - Maria Cristina PEDRAZINI; Vera Cavalcanti ARAÚJO; Victor Angelo Martins MONTALLI (Faculdade São Leopoldo Mandic, 2018)
Several treatments for recurrent herpes labialis have been tested, including intradermal snake venom, camphor compresses, psychiatric treatments, vitamin C and other vitamin complexes. Nowadays, topical and systemic retroviral drugs such as acyclovir, valacyclovir and vadarabina are the drugs of choice. However they are only effective for symptoms minimization of existing lesions, without eliminating the virus permanently. In this study an alternative treatment with oral L-lysine is presented. This is one of the eight essential not manmade amino acids which should be acquired through feeding since they are important for protein synthesis and organism development. It was observed a significant effect on the annual incidence reduction of recurrent herpes in 12 patients with 8-year follow up.